La progettazione scolastica orientata alla promozione della salute. Un percorso di dialogo intersettoriale per l'allineamento delle competenze chiave per l'apprendimento e «life skill» - Maria Grazia Crispiatico; Patrizia Bestetti; Veronica Velasco; Corrado Celata; Liliana Coppola; Gruppo Estensione LST (LED Edizioni Universitarie, 2020)
In health promotion area, the integration of the school and health sectors is essential. The objective of this work is to introduce a logical framework to «align» educational concepts and objectives, starting from international and national indications on school curricula, with health promotion concepts and objectives (in particular life skill and life skill education). A working group composed of 26 school representatives and health promotion professionals has been set up and in a participatory way they have produced alignment tables for different school orders. The tables propose an alignment between: European key competences for lifelong learning, student profile competences, targets for competence development, life skills and LifeSkills Training objectives. The logical framework offers a comparison between different conceptualisations of competences useful for learning and people's well-being. It can also serve as a guideline for school planning competence-based oriented towards health promotion and it can represent an operationalisation of  cross-sectoral collaboration.